In silico Evaluation of Phytochemicals from Calotropis gigantea (L.) Dryand. for Multi-Target Inhibition of Cobra Venom Proteins (International Journal of Pharmaceutical Sciences and Drug Research, 2025)
Snake envenomation leads to about 125,000 deaths yearly in worldwide, with India accounting for almost 50,000 of these fatalities. Even as antivenoms remain the primary treatment, they have got limitations, prompting the exploration of phytochemicals from Calotropis gigantea as potential multi-target therapies against cobra venom toxins. Fourteen venom proteins, namely phospholipase A2 (PLA2), cobrotoxin, L-amino acid oxidase, acetylcholinesterase, cobramin A, cobramin B, cytotoxin 3, long neurotoxins 1 to 5, serine protease and proteolase were the selected targets. The 3D structures of those venom proteins were downloaded from Protein Data Bank and SWISS-MODEL. A complete of 164 phytochemicals from C. gigantea was docked using AutoDock Vina and PyRx 8.0 to assess their binding capability. Compounds with binding energies ≤ -6 kcal/mol have been selected as hits based on their multi-target activity. Subsequently, Absorption, Distribution, Metabolism, Excretion, and Toxicity (ADMET) properties and molecular interactions of these molecules had been analysed, with choice standards specializing in binding affinity and pharmacokinetics. Molecular dynamics simulations over 100 ns, completed the usage of GROMACS 2018.1, identified β-amyrin and lupeol as effective inhibitors of PLA2, acetylcholinesterase, and cobrotoxin. Lupeol exhibited greater constancy throughout simulations, at the same time as β-amyrin more suitable enzyme structure stabilization. Both compounds demonstrated good pharmacokinetics, though issues such as low solubility and potential cardiac dangers warrant further research.